Effect of Red Bean Extract (Phaseolus vulgaris L.) on IL-10 Levels in Systemic Lupus Erythematosus Model - Mukhamad Nooryanto; Tatit Nurseta; Cholid Rohman Riskianto; Syah Sembung Wasiso; Yudistira Yunus (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2023)
Introduction: Systemic Lupus Erythematosus (SLE) is a is a chronic autoimmune inflammatory disease of unknown etiologic. Multiorgan dysfunction in women with SLE causes menstrual irregularities, ovarian failure, follicular atresia, and premature ovarian failure (POF) leading to the cessation of menstruation. Phaseolus vulgaris L. contains isoflavones that can trigger oocyte maturation, stimulate the formation of antral follicles, increase FSH receptor expression and proliferate cell nuclear antigen (PCNA) expression. This study aims to prove the effect of red bean extract (isoflavones) in SLE by and increasing the secretion of anti-inflammatory IL-10 levels. Material and Methods: This study used a true experimental design with a post-test-only controlled group design. The samples used in this study were at least 25 female Balb/c mice. Data on serum IL-10 levels in mice were obtained by measurement using ELISA. The data were statistically analysed using SPSS 16 for Windows software program. The data were tested for normality and homogeneity using parametric non-parametric analysis. Results: The results showed that there was a significant difference in ANA levels with a p-value of 0.000 in each sample. From this test, it was proven that there was a significant increase in IL-10 levels at doses of 75 mg/KgBW (P2) and 100 mg/KgBW (P3) (p-value=0.000) due to the administration of various doses of red bean extract (isoflavones). Conclusion: Red bean extract (isoflavones) had a significant effect in increasing IL-10 levels.